2018
DOI: 10.1111/infi.12144
|View full text |Cite
|
Sign up to set email alerts
|

Economic, institutional, and socio‐cultural determinants of consumer credit in the context of monetary integration

Abstract: We investigated the determinants of consumer credit in relation to nominal GDP in 23 EU countries using panel regressions for 1997–2014. Our contribution to existing research is evidence that both higher density of bank units and greater concentration of the banking sector lead to higher consumer lending. Our results show that the consumer credit to GDP ratio decreases when banking supervision becomes a part of a politically independent central bank. This signals that access to consumer credit is more difficul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…Scientific works of scientists-economists reveal the main provisions of the theoretical foundations of finance, credit and consumption; represent the economic nature and functional purpose of the lending process; contain a theoretical and methodological justification for lending; determine the role of credit operations in the activities of a credit institution; describe in detail the indicators of lending as a sphere of banking activity in a market economy [4][5][6][7][8][9] .…”
Section: Literature Reviewmentioning
confidence: 99%
“…Scientific works of scientists-economists reveal the main provisions of the theoretical foundations of finance, credit and consumption; represent the economic nature and functional purpose of the lending process; contain a theoretical and methodological justification for lending; determine the role of credit operations in the activities of a credit institution; describe in detail the indicators of lending as a sphere of banking activity in a market economy [4][5][6][7][8][9] .…”
Section: Literature Reviewmentioning
confidence: 99%
“…The level of education is a factor that positively influences consumer use of credit. Higher levels of education and better qualifications are a solid basis for higher household creditworthiness, and this provides the possibility of lower margins on consumer credit (Borowski, Jaworski, & Olipra, 2017). On the other hand, the probability of possessing unsecured debt increases with education (Del Rio & Young, 2005).…”
Section: The Determinants Of Household Indebtednessmentioning
confidence: 99%
“…It is pointed out that family size is a good indicator of needs, and debt is likely to increase with such needs. Besides, increasingly indebted households continue to borrow more to sustain their consumption (Borowski, Jaworski, & Olipra, 2017). Research also shows that rising income inequality is linked to increased household indebtedness, and the global financial crisis has shown that this situation has ultimately led to macroeconomic instability.…”
Section: The Determinants Of Household Indebtednessmentioning
confidence: 99%